Intersectional digital feminism: assessing the participation politics and impact of the MeToo movement in China - Yin, Siyuan; Sun, Yu (Feminist media studies, 2021)
Feminist media scholarship has been keen on explicating the ways that digital media have shaped feminist politics in recent decades. Through analyzing the MeToo movement in China, this study contributes to a further understanding of the role of digital media in facilitating feminist activism and movements. We propose a framework of intersectional digital feminism that embraces the perspectives of inclusion/exclusion, visibility/invisibility, and impact/backlash to assess feminist protests and actions in the digital age. The framework also calls for a contextual analysis that accounts for political, social-cultural, and historical circumstances. Drawing upon textual analysis of public and media discourses about China's MeToo movement, the study finds that the formation of the movement in China was attributed to the online and offline formation of feminist, subaltern, and pro-change counter-publics; the backlash came mainly from censorship and misogynistic attacks; and rural and working-class women are largely marginalized and underrepresented in China's present feminist movement. We argue that MeToo manifests both the potential to change gender hierarchies in the digital age and the limitation that structural inequalities cannot be changed by technologies per se. Feminist activism should develop more inclusive agendas and mobilizing strategies pertinent to specific contexts.